Probing the effect on student conceptual understanding due to a forced mid-semester transition to online teaching. (1st May 2022) - Carleschi, Emanuela; Chrysostomou, Anna; Cornell, Alan S; Naylor, Wade
Abstract: The force concept inventory (FCI) can be used as an assessment tool to measure conceptual gains in a cohort of students. The FCI uses a conceptions/ 'misconceptions' lens rather than a context dependent perspective, such as 'knowledge-in-pieces'. In this study it was given to first year students ( N = 256 students) pre- and post-mechanics lectures, at the University of Johannesburg. From these results we examine the effect of switching mid-semester from traditional classes to online classes, as imposed by the COVID-19 lockdown in South Africa. Overall results indicate no appreciable difference of gain, when bench-marked against previous studies using this assessment tool. When compared with 2019 grades, the 2020 semester grades do not appear to be greatly affected. Furthermore, statistical analyses also indicate a gender difference in mean gains in favour of females at the 95% significance level (for paired data, N = 48).